2005
DOI: 10.1177/003335490512000303
|View full text |Cite
|
Sign up to set email alerts
|

Findings from Mental Health Screening of Newly Arrived Refugees in Colorado

Abstract: States are required to provide a public health screening for all newly arrived refugees in the United States. In 1997, a comprehensive program was created to include both a physical examination and a mental health screening. This article provides a complete description of the mental health screening process, including two illustrative cases, and reports information about the refugees who participated in the program. Ten percent of screened refugees were offered mental health referrals; of those, 37% followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 22 publications
2
35
1
Order By: Relevance
“…Practitioners also pointed out the importance of building relationships between agencies (Implication 10), such as between mental health services and schools, other health services and community organisations so that, if the need arises, these agencies are already connected to the mental health services. Similar observations in regards to partnerships (including with religious organisations) were made by Ellis and collaborators (Ellis et al, 2010) and Savin and collaborators (Savin, Seymour, Littleford, Bettridge, & Giese, 2005).…”
Section: Insertsupporting
confidence: 76%
“…Practitioners also pointed out the importance of building relationships between agencies (Implication 10), such as between mental health services and schools, other health services and community organisations so that, if the need arises, these agencies are already connected to the mental health services. Similar observations in regards to partnerships (including with religious organisations) were made by Ellis and collaborators (Ellis et al, 2010) and Savin and collaborators (Savin, Seymour, Littleford, Bettridge, & Giese, 2005).…”
Section: Insertsupporting
confidence: 76%
“…They also reported that "participants who had been released had marked reductions in all psychological symptoms, but those still detained were more distressed than at baseline…detention of asylum seekers exacerbates psychological symptoms" (p. 1721). Similar patterns of depression, Anxiety, and post-traumatic disorders are being reported of refugees in detention across the world (Savin, Seymour, Littleford, Bettridge & Giese, 2005).…”
Section: Communitysupporting
confidence: 59%
“…Based on experiences of large-scale programmes in the US (e.g. Hollifield et al, 2016; Savin et al, 2005), we recommend the inclusion of a mental health screening such as the RHS in the initial medical examination. Refugees with a positive screening result should be offered psychoeducation and if the person wishes so, a referral to mental health services should be organized.…”
Section: Discussionmentioning
confidence: 99%
“…With this goal in mind, state-wide programmes in the USA have included mental health screening in the initial medical examination. They found good results in the feasibility and acceptability of mental health screenings in the public health system (Hollifield et al, 2016; Savin, Seymour, Littleford, Bettridge, & Giese, 2005). Potential barriers in screening and acceptance of referral to mental health services include problems in communication, confidentiality, literacy, stigma, limited care capacities, and difficulties in contacting the refugees (e.g.…”
Section: Introductionmentioning
confidence: 99%